Kepentingan Politik dan Ekonomi Politisasi Bencana: Sebuah Tinjauan Literatur Sistematis - Arif Budiman; Nur Hidayat; Zulhadi (Jurnal Inovasi dan Kreativitas (JIKa), 2024)
Problem: Since the study on manipulating disaster issue for political interest has been easy to find, modus dan motives regarding the action are continuing to vary. It ranges from its simplest form to the sophisticated one. In order to keep update of the issue, renewing cognitive aspects of the theme is a must. Purpose: This research is aimed to enhance the study on disaster politicization, expand disaster mitigation strategy, and strengthen disaster risk management. Method: Systematic literature review Results: Disaster politicisation modus operandi can be found on the form of data expose, mass-fear exploitation, lobbying policy makers, risk shifting management, linguistic politics, and public opinion engineering. Along with political interest of maintaining power is economical interest that is to raise the money out of big disaster management project. Research Type: Qualitative